2021
DOI: 10.1002/clc.23687
|View full text |Cite
|
Sign up to set email alerts
|

Natural language processing for the assessment of cardiovascular disease comorbidities: The cardio‐Canary comorbidity project

Abstract: Objective: Accurate ascertainment of comorbidities is paramount in clinical research. While manual adjudication is labor‐intensive and expensive, the adoption of electronic health records enables computational analysis of free‐text documentation using natural language processing (NLP) tools. Hypothesis: We sought to develop highly accurate NLP modules to assess for the presence of five key cardiovascular comorbidities in a large electronic health record system. Methods: One‐thousand clinical notes were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The performances of our main NLP-ML-CLINICAL pipeline are comparable to the best published results regarding similar approaches, although slightly lower than those reached by Singh et al 13 , 15 , 37 We emphasize that these studies remain difficult to compare as they focus on different languages (French vs English) and texts (eg, Singh et al consider only medical and surgical history sections). Aggregating extractions from the entity level to the stay level significantly improves performances, which is a known and notable result as stay-level or patient-level features are often of higher importance and interest than entity-level features, eg, in epidemiological studies.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The performances of our main NLP-ML-CLINICAL pipeline are comparable to the best published results regarding similar approaches, although slightly lower than those reached by Singh et al 13 , 15 , 37 We emphasize that these studies remain difficult to compare as they focus on different languages (French vs English) and texts (eg, Singh et al consider only medical and surgical history sections). Aggregating extractions from the entity level to the stay level significantly improves performances, which is a known and notable result as stay-level or patient-level features are often of higher importance and interest than entity-level features, eg, in epidemiological studies.…”
Section: Discussionsupporting
confidence: 66%
“…Aggregating extractions from the entity level to the stay level significantly improves performances, which is a known and notable result as stay-level or patient-level features are often of higher importance and interest than entity-level features, eg, in epidemiological studies. 15 Notably, sensitivity is greatly improved, as the aggregation step allows for missed entities of a specific condition to be compensated by other occurrences of the same condition. Similarly, conditions with 2 levels of severity benefit from this aggregation since severity would not necessarily be mentioned on each entity.…”
Section: Discussionmentioning
confidence: 99%
“…The performances of our main NLP-ML-CLINICAL pipeline are comparable to the best published results regarding similar algorithms although slightly lower than those reached by Singh et al . [13,15,36] We emphasize that these studies remain difficult to compare as they focus on different languages (French vs. English) and texts (e.g., Singh et al . consider only medical and surgical history sections).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it was shown that information could be efficiently obtained from clinical notes using Natural Language Processing (NLP) algorithms instead, those algorithms relying even more on machine learning (ML) techniques such as language models. [12][13][14][15][16][17][18][19] Developing tools to this end remains challenging, and many difficulties are yet to be overcome for a wide community to benefit from them. [4,7,[19][20][21][22][23][24] First, the optimal NLP technologies are still debated.…”
Section: Introductionmentioning
confidence: 99%
“…Such techniques offer promising solutions for aiding in the often still manual and labour-intensive process of ICD coding, and for correcting ICD-code related errors. 6 …”
Section: Introductionmentioning
confidence: 99%